OVERVIEW OF WORKING OF STRILING ENGINES - SUNNY NARAYAN; VIKAS GUPTA (Journal of Engineering Studies and Research)
Engines are common devices which are important sources of power to run several devices in modern society. Many of these engines are very complex and need high levels of technological advances for smooth operations. This papers focuses on the identification, design and construction of a Stirling engine which can be easily manufactured without any special tooling or exotic materials. The underlying theory of the device is also presented and discussed with future recommendations to improve the current design.